The Technological Products of the 4th Industrial Revolution From Public R&D Institutions In Indonesia And The Challenges Arising From The Development To The Diffusion Process - Febrianda, Rendi; Ririh, Kirana Rukmayuninda; Romadona, Mia Rahma; Laili, Nur; Maludin, Syafrizal (National Research and Innovation Agency, Indonesia, 2023)
This study was aimed to identify and to compile both the primary and the secondary data of the technological products based on the technology of the 4th industrial revolution developed by public R&D institutions in Indonesia, then to analyze the emerging challenges from the development to the diffusion process. The primary data were obtained through the interview with experts. The secondary data were obtained from each institution’s website, report archives, and written publications. A qualitative analysis using SWOT approach was applied in this study. As the result, this study has identified as many as 33 technological products, in which the 15 products belong to agriculture as the leading sector, followed by fishery, healthcare, and other sectors. The majority of the products’ statuses are prototypes that still require further development. Four main challenges have emerged from the development to the diffusion process: (1) the supporting technologies are mostly imported components and the supplies are not regularly available; (2) the disbursement of the components budget is considered complicated; (3) there is no potential licensing with the private sectors; and (4) the diffusion of the products is considered difficult when it comes to deal with the users that have low level of digital literacy. Keywords: 4th industrial revolution, public R&D institution, technology, challenge, Indonesia